HUBUNGAN PARITAS DENGAN KEJADIAN PLASENTA PREVIA DI RSUD DR. CHASBULLAH ABDULMADJID KOTA BEKASI TAHUN 2018 - Siantar, Rupdi lumban (Jurnal Ayurveda Medistra, 2020)
Parity is the number of deliveries a mother has experienced, both live and stillbirth. Parity is divided into 3, namely: a) Primipara: a woman who has given birth once to a baby who has reached the stage of being able to live. b) Multipara: woman who has given birth to two or more fetuses. c) Grandemultipara: woman who has given birth to five or more children. In multiparous women placenta previa often occurs. In multipara placenta previa occurs due to reduced vascularization and atrophy in the decidua caused by previous labor which can cause the placenta to expand its surface and close the birth canal. Objective: To find out the relationship between parity and the incidence of placenta previa in RSUD dr. Chasbullah Abdulmadjid Bekasi City in 2018. Method: This type of research is cross sectional. The population in this study was maternity mothers who experienced placenta previa in RSUD dr. Chasbullah Abdulmadjid Bekasi City in 2018. The method used is Probability sampling with Simple Random Sampling technique and using the Slovin formula. Results: Statistical test results obtainedp= 0,001 (p<0,05) which means that there is a relationship between parity and the incidence of placenta previa. Conclusion: There is a Parity Relationship with the Occurrence of Placenta Previa in Dr.Chasbullah Abdulmadjid Regional Hospital, Bekasi City in 2018. Keywords : Parity and placenta previa Reference list :(2010-2018) Number of pages : XLI + 41